PARADIGAMA PENDIDIKAN ISLAM PEMBEBASAN - Syarif, Zainuddin (Institut Agama Islam Negeri Madura)
AbstractLiberation- paradigmatic Islamic education tries to abdicate human from any threats. It is to grow the boldness to obey and submit Allah swt. Substantially, Islam is always in effort to appreciate human in equal degree, maintain the humanity, higly supports the values democration and justice, teaches telling the truth, and loves the poor and the oppressed. Kata-kata kuncipendidikan islam, pembebasan,